Power plyometrics the complete program - McNeely, Ed (Meyer & Meyer Sport, 2007)
Plyometrics is a training technique used by many top athletes to improve their speed and power. This volume allows the reader to assess their individual needs and performance level, and then progress through three increasingly challenging training levels until they are ready to train for their specific sport.